The tongue, the text and the tape recorder. Vernacular and the technology of writing in Ralf Andtbacka's Wunderkammer. Issue 5 (3rd May 2020) - Tidigs, Julia
ABSTRACT: Finland-Swedish poet Ralf Andtbacka's (b. 1963) Wunderkammer (2008) is ripe with languages, jargons, intertextual references and encyclopedic excerpts fusing historical marginalia, transatlantic poetic influences and locally inscribed language. Wunderkammer explores the dynamics between orality and technology and between language and desire through the discussion and artistic use of the vernacular, most prominently dialectal, Ostrobothnian Swedish. Thematically and linguistically, the collection confronts its readers with a process where spoken words, as sounds, are transposed into visual objects on the book page. Furthermore, Wunderkammer engages with the historical legacy of Finland-Swedish language regulation where the vernacular has been trapped in a force field defined by the poles of purity vs. authenticity. In this article, I explore the aesthetic and political ramifications of the dynamics of Ostrobothnian dialect and technologies aimed at recording or reproducing the vernacular in Wunderkammer. These technologies include the literary work itself, and in this context, Andtbacka's erotic poem 'Tongknoll' heavily featuring the vernacular is central. From a perspective of literary multilingualism, multimodality and reader experience, I argue that Wunderkammer envisages a sensorially acute reimagining of difference, not only in terms of linguistic orders and borders but also through the enactment of the malleability of the border between language and noise.